Investigation of machining performance in ecdm of Al6061-SiC-B4C hybrid composites - Safa Lafta; Abbas Ibrahim (Engineering and Technology Journal, 2025)
This study investigates the machining performance of the Electrochemical Discharge Machining (ECDM) process on a hybrid composite material comprising Aluminum 6061 reinforced with 6% silicon carbide (SiC) and 6% boron carbide (B4C). Experiments evaluated the effects of electrolyte concentration, voltage, pulse-on time, and pulse-off time on Material Removal Rate (MRR), Tool Wear Rate (TWR), and Surface Roughness (SR). Taguchi analysis and ANOVA highlighted the significant influence of these parameters on machining outcomes. The optimal MRR (0.113 g/min) was achieved at 20% electrolyte concentration, 40V, 150 µs pulse-on time, and 25 µs pulse-off time. The best TWR (0.007 g/min) occurred at 30% concentration, 30V, 150 µs pulse-on time, and 50 µs pulse-off time. The optimal SR (4.757 µm) was observed at 20% concentration, 30V, 100 µs pulse-on time, and 75 µs pulse-off time. The findings emphasize the importance of parameter optimization in improving machining efficiency and surface integrity, offering valuable insights for hybrid composite applications. In particular, the study reveals that higher electrolyte concentrations and voltages generally enhance MRR but can increase TWR and degrade SR. These findings underline the importance of parameter optimization for balancing productivity and surface integrity. This research provides valuable insights for industries seeking precise and efficient machining of hybrid composites, showcasing a 34% enhancement in machining efficiency and a 21% improvement in surface quality using the optimized ECDM conditions.